MENINGKATKAN KEUNGGULAN BERSAING MELALUI HARGA PADA UKM KOTA BATAM - Herman, Hendri (Postgraduate Management Journal, 2021)
This study aims to look at the influence of price in determining the advantages of the cross-legged and how much the influence of price on competitive advantage. The sample in this study was 92 respondents. The result of this study is known that price has a significant influence on the competitive advantage of a company. The amount of price influence on competitive advantage is 43.7%.. This price influence has a considerable influence on the competitive advantage of the company. Therefore, companies or businesses need to special attention in determining the selling price of products